ANALISIS KESESUAIAN PENGGUNAAN LAHAN BERDASARKAN KELAS KEMAMPUAN LAHAN DI DAS MAROS - Tasya Febrina Utami; Soma, Andang Suryana; Wahyuni, W (Forestry Faculty of Hasanuddin University, 2023)
Land use change in the Tanralili sub-watershed (upstream of the Maros watershed) is the main cause of decreased vegetation density and landslides. This study aims to identify land capability classes, analyze the suitability of land use with land capability classes and formulate land use directions based on Maros watershed land capability classes. The data obtained from laboratory analysis determined the land capability class; the land cover map was overlaid with the land capability class map to determine the suitability of land use and the next direction. The results of the land capability classification in the Maros watershed obtained six land capability classes, with Class IV dominating the land study with a total area of 37,792.34 ha (62.11%). The Maros watershed has 24,714.18 ha (40.62%) of unsuitable land. The direction for land management carried out on unsuitable land units is to direct community forestry activities (HKm) with an agroforestry system on the use of dryland agricultural land within forest areas through a supported talun-garden and grass-forest (silvopasture) model approach with vegetative conservation efforts.